Modern approaches to diagnostics of hyperandrogenism distributed forms in reproductive aged women - О. А. Бурка; М. І. Бобрик; В. М. Резниченко; Т. М. Тутченко (Publishing House TRILIST, 2019)
PCOS is a widespread endocrine disorder of polymorphic ethiology and pathogenesis and varying phenotypic forms that has negative effect non only on reproductive function but also on glucose and lipid metabolism, cardiovascular health, psychological wellbeing and oncologic risks throughout all life of women and their offsprings. Diagnosis of PCOS is based upon at least 2 of the 3 criteria: clinical/biochemical hyperandrogenism, olygo-anovulation, polycystic ovarian morphotype on ultrasound. Exclusion of all other causes of hyperandogenism and anovulation is mandatory. PCOS women both with and without obesity or overweight have significantly higher risk of glucose metabolism disorders and dyslipidemia starting from reproductive age, which leads to diabetes mellitus and cardiovascular disease in older age. Interconnected processes of hyperandrogenism and insulin resistance are the main causes of high risks of cardiometabolic complications in women with PCOS. At the same time PCOS is among risk factors of DM2 which makes screening of all women with PCOS for disglycemia irrespectable of BMI reasonable. Evaluation of insulin resistance in PCOS in clinical setting may be complicated. Contemporary laboratory tests make diagnosis of all stages of dysglicemia from insulin resistance to diabetes possible as well as monitoring of applied interventions (lifestyle modification, medications). Thus, contemporary management of PCOS implies not only correction of reproductive disorders but also prevention of metabolic risks and comorbidities lifelong starting from the moment PCOS is diagnosed.